“Nos llaman ladrones y se roban nuestro salario”: Hacia una reinterpretación de la movilización rural salvadoreña, 1929-1931 - Lauria Santiago, Aldo; L. Gould, Jeffrey (Revista de historia., 2005)
This article delves into the social origins of the movements that triggered the 1932 peasant revolt in the central-western region of El Salvador. The authors used new oral and documentary sources to outline the way in which reformism, the economic crisis, and the communist activism managed to break the ethnic and regional barriers that divided the western peasantry and fostered a massive mobilization.